Labour supply modelling in Italy when minimum income scheme is an option - Edlira Narazani; Isilda Shima (University of Essex, Institute for Social and Economic Research (ISER), 2008)
In this paper we analyze the effects of Minimum Guaranteed Income (MGI) schemes on labour supply of Italian married couples by applying a behavioural micro-simulation tax-benefit model. The Tax-Benefit Model applied is the static micro-simulation model of EUROMOD. A household labour supply model is simulated with different tax rules where MGI is an option. The simulated tax regimes are Negative Income Tax (NIT), Workfare Tax (WF) and Universal Basic Income (UBI). These exercises of behavioural micro-simulation tax-benefit are performed at national and regional level. Our main finding is that changes in labour supply due to these tax-transfer rules are small and this is in favour of such income support policies. Concerning tax-transfer rules without hour's constraint, such as UBI and NIT, they imply labour disincentives more in the South than in the North of the country, and the effect is amplified with the increase of generosity level. Considering the welfare effects of these tax-transfer rules, we find that there are more winners than losers in the south than in the north as there are more households participating in these MGI schemes due to their low income status.
Keywords: C25; H24; H31; I38; 330; Labour Supply; Discrete Choice Model; Minimum Guaranteed Income; Regional Differences; Mindestlohn; Steuerpolitik; Arbeitsangebot; Familie; Regionale Disparität; Italien